Social work treatment : interlocking theoretical approaches - Turner, Francis J.; Angell, Brent G. (New York : Oxford University Press Inc., 2017)
First published in 1974, Social Work Treatment remains the most popular and trusted compendium of theories available to social work students and practitioners. It explores the full range of theoretical approaches that drive social work treatment and knowledge development, from psychoanalysis to crisis intervention. A treasure trove of practice knowledge, the text equips professionals with a broad array of theoretical approaches, each of which shine a spotlight on a different aspect of the human condition. Emphasizing the importance of a broad-based theoretical approach to practice, it helps readers avoid the pitfalls of becoming overly identified with a narrow focus that limits their understanding of clients and their contexts. This sweeping overview of the field untangles the increasingly complex problems, ideologies, and value sets that define contemporary social work practice. The result is an essential A-to-Z reference that charts the full range of theoretical approaches available to social workers, regardless of their setting or specialty.
1. Attachment Theory and Social Work Treatment / Timothy Page. -- 2. Brain Plasticity: An Emerging Therapeutic Technique for Social Work / Dan Andreae. -- 3. Chaos Theory and Social Work Treatment / Sandra Loucks Campbell. -- 4. Client-Centered Theory and the Person-Centered Approach: Values-Based Evidence-Supported / William S. Rowe. -- 5. Cognitive Behavior Theory and Social Work Treatment / Ray J. Thomlison and Barbara Thomlison. -- 6. Cognitive Theory and Social Work Treatment / Pranab Chatterjee and Suzanne Brown. -- 7. Constructivism: A Conceptual Framework for Social Work Treatment / Donald E. Carpenter and Keith Brownlee. -- 8. Crisis Theory and Social Work Practice / Diane Mirabito. -- 9. Ecopsychology: Adding "Eco" to the Biopsychosocialspiritual perpespctive / David Derezotes. -- 10. Empowerment Approach to Social Work Treatment / Judith A.B. Lee and Dr. Rhonda E. Hudson. -- 11. Existential Social Work / Donald Krill. -- 12. Feminist Theory and Social Work Practice / Eveline Milliken. -- 13. The Four Forces: An Inclusive Model / Au-Deane Shepherd Cowley. -- 14. Functional Theory and Social Work Practice / Katherine M. Dunlap. -- 15. General Systems Theory: Evolution and Application / Nancy Riedel Bowers and Anna Bowers. -- 16. Gestalt Theory and Social Work Treatment / Elaine P. Congress. -- 17. Hope Theory and and Social Work Treatment / Alexander T. Polgar. -- 18. Hypnosis and Clinical Social Work Practice / Elayne Tanner. -- 19. Life Model of Social Work Practice: An overview / Alex Gitterman. --21. Mindfulness and Social Work / Kirstin Bindseil and Kate Kitchen. -- 22. Narrative Theory and Social Work Treatment / Patricia Kelley and Mark Smith. -- 23. Neurolinguistic Programming Theory and Social Work Treatment / Brent Angell. -- 24. Oppression Theory and Social Work Treatment / Susan P. Robbins. -- 25 Problem-Solving and Social Work / Michael L. Shier. -- 26. Psychoanalytic System of Ideas / Elizabeth Ann Danto. -- 27. The Psychosocial Framework of Social Work Practice / Emilia E. Martinez-Brawley and Paz M B Zorita. -- 28. Relational Social Work: A Contemporary Psychosocial Perspective on Practice / Carol Tosone and Caroline Rosenthal Gelman. -- 29. Relational Theory and Social Work Treatment / Dennis Miehls. -- 30. Resilience Theory / Robbie Gilligan. -- 31. Role Theory and Concepts Applied to Personal and Social Change in Social Work Treatment / Dennis Kimberley and Louise Osmond. -- 32. Social Learning Theory and Social Work Treatment / Bruce A. Thyer. -- 33. Social Networks and Social Work Practice / Elizabeth M. Tracy and Suzanne Brown. -- 34. Social Work Practice in the Time of Neuroscience / Robert J. MacFadden. -- 35. Socially Costructing Social Work / Dan Wulff. -- 36. Solution-Focused Theory / Mo Yee Lee. -- 37. Task-Centered Social Work / Anne E. Fortune and William J. Reid. -- 38. Trauma Informed Social Work Treatment and Complex Trauma / Dennis Kimberley and Ruth Parsons. -- 39. Emerging Theories / Emilia E. Martinez-Brawley. -- Epilogue: Social Work Treatment VI: Some Final Comments.
Keywords: Social service; sosiaalityö; teoriat; työmenetelmät; käytäntö